The Influence Of Commitment And Emotional Intelligence On The Turnover Intention Of Marriage Partners At The Sub-District Kua In Muara Enim District - Lin Yan Syah; Imam Izharyanto; Nisma Aprini (UNIVED Press, 2024)
The purpose of this study was to determine and analyze the effect of commitment and emotional intelligence on the turnover intention of married couples at the District Office of Religous Affairs (KUA) in the Muara Enim Regency area. The sampling technique used is purposive sampling technique, with a descriptive approach. The data collection method uses questionnaires and interviews. The questionnaire uses a Likert scale. This study used the Structural Equation Modeling (SEM) data analysis technique, with the LISREL (Linear Structural Relation) tool verson 8.7. The result of the study concluded that commitment has a significant effect on the turnover intention of married couples at the District Office of Religous Affairs (KUA) in the Muara Enim Regency area with a regression coefficient of 1.00 and t-value = 7,34, and emotional intelligence has a significant effect on the turnover intention of married couples at the District Office of Religous Affairs (KUA) in the Muara Enim Regency area with a regression coefficient of 1.00 and t-value = 5,15.